Little cloud - Carle, Eric ([S.l.] Puffin Books, 2001)
A little cloud becomes all sorts of things--a sheep, an airplane, trees, a hat--before joining other clouds and raining.
"Ages 2-6."
Keywords: Clouds -- Fiction